Contributions to the distribution and ecology of Carex hordeistichos Vill. in the Czech Republic and Slovakia - Dítě, Daniel; Grulich, Vít; Eliáš, Pavol (Biodiversity: Research and Conservation, 2011)
Current and historical occurrence as well as habitat requirements of Carex hordeistichos in the Czech Republic and Slovakia are presented. The study is based on the revision of herbarium specimens from 25 herbaria and a field survey carried out during 2004-2009. Altogether, 195 sites were documented in the Czech Republic, exclusively in the Moravia region. Recent occurrence was confirmed at only four localities (2% of sites), therefore the status of threat was confirmed - the species is critically endangered. In Slovakia, 184 localities of the species were recorded in total; 34 sites were found in period 1975-1999 and 35 sites were confirmed recently (19% of sites recorded), but only 6 in the Pannonia (3% of sites). The number of localities was stable over the last 35 years, therefore, we re-evaluated the IUCN status of C. hordeistichos in Slovakia. The species is now assessed in the category vulnerable - VU. Results of the study are summarised in the maps of historical and actual species distribution. C. hordeistichos usually occurred in various wet grassland communities and it had no well-defined coenotic relationships. On the basis of our knowledge, we consider C. hordeistichos as a facultative halophyte.